[Jóka Gémesi 3]
american film details, sailors, "Great Smoky National Park, joiner's workshop, pottery, "The Boy Scouts of America Presents Senior Scouting, nice rocky mountains with a lake, cartoon details, "Vintage in Sátoraljaújhely", "Kunság Puszta" puszta show, "Tenessee Holiday", country, towns, people, work, amusment